Improving the Speaking Ability at the Second Grade Students of SMKN 1 Watunohu Through Media Picture - Afif, Muhammad (USN Kolaka, 2022)
This study aimed to investigate the improvement of students’ speaking ability through the use of picture media. The participants were 25 second-grade students of SMKN 1 Watunohu. The study employed a classroom action research (CAR) design, which was conducted over two cycles. Each cycle involved planning, implementing, observing, and reflecting stages to identify the effectiveness of picture media in enhancing students’ speaking skills. Data were collected through speaking tests, classroom observations, and field notes, focusing on students’ ability to introduce someone, retell the profile of a picture, and describe someone based on the picture’s profile. The findings revealed a significant improvement in students’ speaking ability across the two cycles. In the first cycle, the average speaking score was 55.4, indicating a moderate level of proficiency. After implementing the second cycle with refined strategies and feedback, the average score increased to 77.6, demonstrating substantial improvement. Observational data also showed that students were more confident, engaged, and able to express ideas fluently when supported by visual aids. The results suggest that picture media serves as an effective tool for developing speaking skills by providing contextual and visual support, stimulating students’ ideas, and facilitating meaningful communication. In conclusion, the use of picture media in the teaching and learning process significantly enhances students’ speaking ability, particularly in tasks such as introducing others, retelling profiles, and describing people based on visual cues. This study provides evidence that integrating visual media into English language teaching can increase learners’ motivation, participation, and overall language proficience.